A harmonised definition of cities and rural areas: the new degree of urbanisation. - Dijkstra, Lewis; Poelman, Hugo (My University, 2014)
This paper describes the new degree of urbanisation (DEGURBA) classification. This classification distinguishes three types of areas: densely, intermediate and thinly populated areas. This new approach was developed to harmonize several similar but not identical spatial concepts. The new classification is based on a new source of information: the population grid. This paper shows the benefits of this approach in terms of greater comparability and data availability. It describes the method and how it was developed. The annex contains the original and the new guidance notes on the degree of urbanisation and a section on how to update the degree of urbanisation. It also contains the United Nations (UN) recommendations on localities and urban/rural areas and the definitions of urban areas used in Europe in a recent United Nations Population Division (UNPD) report.
Keywords: Siedlungsstruktur; Siedlungsentwicklung; Verstädterung; Raumentwicklung; Region; Siedlungsdichte; Bevölkerungsdichte; Raumgliederung; Raumabgrenzung; Raumwissenschaft; Raumordnungspolitik; Regionalpolitik; International; Klassifikation; Raumtyp; Raumkategorie